Trogonoptera brookiana mollumar d’Abrera, Doggett & Parker, 1976 (Lepidoptera: Papilionidae), a subspecies or a synonym? - Phon, Chooi Khim; Kirton, Laurence G.; Norma-Rashid, Yusoff (Consortium of European Natural History Museums, 2019)
The birdwing butterfly Trogonoptera brookiana (Wallace, 1855) is a well-known conservation icon, yet questions remain about the infraspecific status of regional populations. The eastern Peninsular Malaysian population has been described as the subspecies mollumar d’Abrera, Doggett & Parker, 1976, but its status as a subspecies distinguishable from the taxon trogon (Vollenhoven, 1860) in Sumatra has been disputed. Wing characters and measurements of specimens from the two regions were therefore examined quantitatively using discriminant function and correspondence analyses. Eastern Peninsular specimens differ on average from Sumatran specimens in having more extensive green, especially in the female. This is reflected in many of the measurements and characters analysed. Females from the Peninsula also have a characteristically blacker upperside ground colour in which the outer areas of both wings barely contrast with the black veins and forewing cell. The extent of these differences enables a reliable differentiation of the females of both regions. The magnitude and consistency of differences are comparable to that between other subspecies of undisputed status. Behavioural differences also exist. The name mollumar therefore merits subspecific status. In addition, we consider the male forms walshi Haugum & Low, 1982 and walshoides Haugum & Low, 1982 to be chemically discoloured specimens of trogon rather than biological forms. © 2019, Museum National d'Histoire Naturelle. All rights reserved.